Recent advances in nanomaterials and their mechanisms for infected wounds management - Jianping Zhu; Fan Xia; Shuaifei Wang; Yan Guan; Fuqiang Hu; Fangying Yu (Materials Today Bio)
Wounds infected by bacteria pose a considerable challenge in the field of healthcare, particularly with the increasing prevalence of antibiotic-resistant pathogens. Traditional antibiotics often fail to achieve effective results due to limited penetration, resistance development, and inadequate local concentration at wound sites. These limitations necessitate the exploration of alternative strategies that can overcome the drawbacks of conventional therapies. Nanomaterials have emerged as a promising solution for tackling bacterial infections and facilitating wound healing, thanks to their distinct physicochemical characteristics and multifunctional capabilities. This review highlights the latest developments in nanomaterials that demonstrated enhanced antibacterial efficacy and improved wound healing outcomes. The antibacterial mechanisms of nanomaterials are varied, including ion release, chemodynamic therapy, photothermal/photodynamic therapy, electrostatic interactions, and delivery of antibacterial drugs, which not only combat bacterial infections but also address the challenges posed by biofilms and antibiotic resistance. Furthermore, these nanomaterials create an optimal environment for tissue regeneration, promoting faster wound closure. By leveraging the unique attributes of nanomaterials, there is a significant opportunity to revolutionize the management of infected wounds and markedly improve patient outcomes.